4(m-2)-8+2m=6(m+5)

Simple and best practice solution for 4(m-2)-8+2m=6(m+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(m-2)-8+2m=6(m+5) equation:


Simplifying
4(m + -2) + -8 + 2m = 6(m + 5)

Reorder the terms:
4(-2 + m) + -8 + 2m = 6(m + 5)
(-2 * 4 + m * 4) + -8 + 2m = 6(m + 5)
(-8 + 4m) + -8 + 2m = 6(m + 5)

Reorder the terms:
-8 + -8 + 4m + 2m = 6(m + 5)

Combine like terms: -8 + -8 = -16
-16 + 4m + 2m = 6(m + 5)

Combine like terms: 4m + 2m = 6m
-16 + 6m = 6(m + 5)

Reorder the terms:
-16 + 6m = 6(5 + m)
-16 + 6m = (5 * 6 + m * 6)
-16 + 6m = (30 + 6m)

Add '-6m' to each side of the equation.
-16 + 6m + -6m = 30 + 6m + -6m

Combine like terms: 6m + -6m = 0
-16 + 0 = 30 + 6m + -6m
-16 = 30 + 6m + -6m

Combine like terms: 6m + -6m = 0
-16 = 30 + 0
-16 = 30

Solving
-16 = 30

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| Ax+4y+4x+ay= | | x=1.04*y+6.18 | | 2x+3y+1z=51.4 | | X^3/3=65 | | X/3=65 | | 6(y-5)=4(y+2) | | 5y=10x+2 | | x*2-8=8 | | 5n+4=2n+33 | | 3(a+7)=36 | | a^5+4=15 | | C/3C | | 4x-11=46 | | 3x+5=-8x-4 | | 4t-9=0 | | 7m+5=55 | | 1.74x+x=.1 | | 6h-3=15 | | 3g+6=15 | | x/3+x/12=15/4 | | 4/x=5/-6 | | 3n^2+6n-13=0 | | R=ir | | (2x-3)*(2x-3)=25 | | 6+6x=4x-10 | | Y=(x-2)(x+3) | | 4sint+3cost=0 | | 3x+30=2x-10 | | Y=(x+4)(x+1) | | Y=(x+4)(c+1) | | 12w=14 | | w/4=7.2 |

Equations solver categories